Stress and Coping Strategies among Parents of Hospitalized Children in Selected Tertiary Hospitals, Kathmandu - Ranjitkar, Uma Devi; Adhikari, Sushila; Pandey, Apsara (Journal of Nursing Education of Nepal, 2024)
Introduction: Hospitalization for a child can lead to anxiety, depression, and stress for parents, impacting their psychological health and treatment adherence, ultimately affecting the child’s health outcomes. This study aimed to find out stress and coping strategies among parents of hospitalized children in selected tertiary hospitals in Kathmandu. Methods: A cross-sectional descriptive study was conducted among 200 parents of hospitalized children in two tertiary hospitals in Kathmandu. Non-probability purposive sampling technique was used. Data were collected using Depression, Anxiety, and Stress Scale and the Coping Health Inventory for Parents. In-person interview method was used to collect data. Data analysis was done using SPSS Version 20.0. Ethical approval was obtained from the Ethical Review Board, Nepal Health Research Council. Results: Among the parents studied, 53.0% were mothers of hospitalized children. Regarding parental stress, 71.5% had a normal level of stress; 12.0%, 9.0%, 5.0%, and 2.5% of the parents had mild, moderate, severe, and extremely severe level of symptoms of stress respectively. There is a significant association of parental stress with their education level (p = 0.029), family income (p=0.032), adequate number of toilets and bathrooms (p=0.27), supply of medicine (p=0.040), and the crowded and noisy environment of the hospital (p = 0.009). Parents used various coping strategies to reduce stress: maintaining family unity, cooperation, and optimism (mean score± SD 23.94± 4.60); seeking social support and emotional stability (mean score± SD: 25.80± 5.38); and understanding their child’s medical situation through communication with other parents and healthcare professionals (mean score± SD 12.65±2.95). Conclusions: Parents experience stress during hospitalizations, influenced by education, income, toilet availability, medicine supply, and noise. They employ various coping strategies. Hospitals should enhance their facilities and communication, reduce environmental stressors, and promote coping strategies for parents of children in the hospital, especially for those with lower education or income.